The Asian Eyelid: Relevant Anatomy - Kiranantawat, Kidakorn; Suhk, Jeong Hoon; Nguyen, Anh H. (Seminars in Plastic Surgery, 2015)
The eyelid of Asians has its own unique characteristics. If the surgeon does not acknowledge this, aesthetically pleasing results will seldom be achieved. Here the authors review and summarize important up-to-date anatomical and relevant clinical studies of the Asian upper eyelid, aiming to help surgeons thoroughly understand its unique features, including Asian eyelid morphology, anatomical details, and the mechanisms of upper eyelid crease formation. Hopefully, an in-depth understanding of the Asian eyelid will aid surgeons to accomplish their work and lead to novel new techniques in this field.
Keywords: Asian eyelid anatomy; Asian eyelid; eyelid anatomy; Asian eyelid morphology; Asian blepharoplasty; Asian double crease